Acquired Reactive Perforating Collagenosis: Clinicopathologic Analysis of 12 Cases - Zhang Q; Chang J (Clinical, Cosmetic and Investigational Dermatology)
Qiuli Zhang, Jianmin Chang Department of Dermatology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People’s Republic of ChinaCorrespondence: Jianmin Chang, Department of Dermatology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, No. 1 DaHua Road, Dong Dan, Beijing, 100730, People’s Republic of China, Tel +86-10-85133303, Email changjianmin@medmail.com.cnBackground: Acquired reactive perforating collagenosis (ARPC) is a rare and complex dermatological condition often associated with systemic diseases such as diabetes and chronic kidney disease. It is characterized by the transepidermal elimination of collagen fibers. ARPC presents with diverse clinical manifestations, leading to frequent misdiagnosis. This study provided a comprehensive overview of the clinical pathology and treatment outcomes in 12 confirmed cases of ARPC. The findings aimed to enhance clinicians’ understanding of this condition and inform better diagnostic and therapeutic strategies.Methods: A retrospective analysis was carried out to summarizes the clinical pathology and treatment response of the ARPC.Results: The patients had a mean age of 60.2 years, with a predominance of female cases. The primary clinical features included papules and nodules predominantly affecting the lower limbs, with central ulceration, necrosis, and severe pruritus. Histopathological examination showing cupped epidermal invagination containing crusts, inflammatory cells, and degenerated collagen; degenerated collagen fibers penetrating vertically through the epidermis. Treatment primarily involved topical therapies, while dupilumab demonstrated efficacy in some refractory cases.Discussion: Early diagnosis and intervention of ARPC are crucial for improving patients’ quality of life. Further research is needed to elucidate the pathological mechanisms and management strategies of ARPC. Exploring its pathogenesis and biological characteristics remains pivotal for advancing diagnostic and therapeutic approaches.Keywords: reactive perforating collagenosis, acquired, histopathology, Masson staining